HUBUNGAN PENINGKATAN KADAR C-REACTIVE PROTEIN DENGAN PENURUNAN FUNGSI KOGNITIF PASIEN GERIATRI RAWAT JALAN - Stefanus Erdana Putra; Muhammad Hafizhan; Raden Ajeng Hanindia Riani Prabaningtyas (PERDOSNI, 2019)
THE RELATIONSHIP BETWEEN ELEVATED C-REACTIVE PROTEIN AND COGNITIVE FUNCTION DETERIORATION OF GERIATRIC OUTPATIENTSABSTRACTIntroduction: Geriatric patients have different characteristics compared to other patients in general, in which they potentially experiencing cognitive impairment, decreasing of physiological and functional status, also the immunological system. This situation causes various inflammatory reactions that play a role in the development of neurodegenerative diseases, including the increase production of acute phase protein called C-reactive protein (CRP).Aims: To determine the association between the CRP serum concentration elevation and the deterioration of geriatric outpatients’s cognitive function at Neurology Clinic Sebelas Maret University Hospital.Methods: A cross-sectional study of geriatric patients at the Neurology Clinic of Sebelas Maret University Hospital, Surakarta. The cognitive state was evaluated using Mini-Mental State Examination (MMSE) and those with MMSE score<24 were considered cognitively declined. Concentrations of serum CRP were measured. Multiple logistic regression analysis was used to calculate Odds ratios (ORs) for cognitive decline, adjusted for the covariates of age, sex, body mass index, and disease history.Results: There were 73 participants with mean age was 65.6 years old. There were 56,2% who were experiencing a cognitive decline. Relative to the lowest (first) quartile of CRP concentration, adjusted ORs were 1,44 for the second, 1,97 for the third, and 2,33 for the highest quartiles (p=0,035). The association between CRP levels and decreased cognitive function was found to be significant after adjusting for covariates. When data were stratified by sex, the association between CRP concentration and cognitive decline was observed in women.Discussions: This research suggested an association between higher CRP concentration and lower cognitive function. Chronic inflammation might affect cognitive function in geriatric, particularly in women.Keywords: C-reactive protein, cognitive function, geriatric outpatientsABSTRAKPendahuluan: Pasien geriatri memiliki karakteristik yang berbeda dengan pasien pada umumnya, yaitu selain berpotensi mengalami gangguan fungsi kognitif juga menurunnya daya cadangan fisiologis serta status fungsional dan sistem imunologi. Keadaan ini menimbulkan berbagai reaksi inflamasi yang berperan dalam perkembangan penyakit neurodegeneratif, antara lain peningkatan produksi protein fase akut bernama C-reactive protein (CRP) oleh hepar.Tujuan: Mengetahui hubungan antara peningkatan kadar CRP dengan penurunan fungsi kognitif pasien geriatri rawat jalan di Poliklinik Saraf RS Universitas Sebelas Maret.Metode: Penelitian potong lintang terhadap pasien geriatri di Poli Saraf RS Universitas Sebelas Maret, Surakarta. Evaluasi fungsi kognitif menggunakan Mini-Mental State Examination (MMSE); dengan skor <24 dikategorikan mengalami penurunan fungsi kognitif. Kadar serum CRP masing-masing subjek juga diukur. Analisis regresi logistik berganda digunakan dalam menghitung rasio Odds (RO) untuk penurunan fungsi kognitif, dengan pengaturan kovariat usia, jenis kelamin, indeks massa tubuh, dan riwayat penyakit sebelumnya.Hasil: Didapatkan 73 subjek dengan rerata usia 65,6 tahun. Sebanyak 56,2% subjek mengalami penurunan fungsi kognitif. Dengan perbandingan relatif terhadap kuartil konsentrasi CRP terendah (pertama), RO yang telah diatur adalah 1,44 untuk kuartil kedua; 1,97 untuk kuartil ketiga; serta 2,33 untuk kuartil keempat (p=0,035). Hubungan kadar CRP dan penurunan fungsi kognitif ditemukan signifikan setelah disesuaikan dengan kovariat. Setelah dilakukan sub-analisis berdasarkan jenis kelamin, peningkatan kadar CRP terhadap penurunan kognitif secara signifikan terjadi pada subjek perempuan.Diskusi: Penelitian ini menunjukkan adanya hubungan antara peningkatan kadar CRP dengan penurunan fungsi kognitif. Inflamasi kronis memengaruhi fungsi kognitif geriatri khususnya perempuan.Kata kunci: C-reactive protein, fungsi kognitif pasien rawat jalan, geriatri